ANALISIS TOTAL QUALITY MANAGEMENT (TQM) DAN KINERJA MANAJERIAL PADA POLITEKNIK RAFLESIA REJANG LEBONG - Niarti, Upi; Nurazi, Ridwan; Coryanata, Isma (JURNAL FAIRNESS, 2016)
This research is a descriptive analysis that compares theory with its implementation, namely the analysis of Total Quality Management (TQM) and managerial performance in higher education organizations.The data were obtained through a questionnaire on the management of the Raflesia polytechnic and its customers. The analytical method used is qualitative data analysis according to the model of Miles and Huberman (1984).The results showed that the implementation of the TQM concept according to the theory of Tenner and DeToro at the Raflesia Rejang Lebong Polytechnic has been carried out "quite well" in certain parts but in other parts, there is still need to be improvement by management in the future. As for managerial performance, the results show that the management performance of the Raflesia Polytechnic has been running quite well.